International financial management - Agarwal, O. P. (Himalaya Pub. House, 2009)
CHAPTER-l Multinational Corporation and its International Environment CHAPTER-2 Multinational Corporation - its rational goals and constraints CHAPTER-3 International financial markets CHAPTER-4 Offshore Banking Centres and Management of Risks CHAPTER- 5 Foreign Exchange Risks CHAPTER - 6 Balance of Payments CHAPTER-7 International Banking CHAPTER-8 Foreign Exchange Market CHAPTER-9 Exchange Rate Quotation and Determination CHAPTER-I0 Option Forwards and Swap CHAPTER -11 International Financial Institutions CHAPTER -12 Multinational Capital Budgeting CHAPTER-13 Cost of Capital and Financial Structure CHAPTER -14 Long Run Investment Decisions CHAPTER-15 International Transfer Pricing CHAPTER -16 International Monetary System CHAPTER-17 Globalisation and Financial Deregulation CHAPTER -18 Monetary Theories of Exchange Rate Determination and Exchange Rate Risk CHAPTER -19 International Financial Markets CHAPTER - 20 Foreign Trade CHAPTER - 21 Instruments of Foreign Trade CHAPTER- 22 Cross Border Financing - Export Finance - Pre shipment CHAPTER- 23 Cross Border Export Finance - Post-shipment CHAPTER - 24 International Accounting CHAPTER - 25 International Working Capital Management CHAPTER - 26 Case Studies Bibliography.